2013
DOI: 10.1097/iop.0b013e31829bb14b
|View full text |Cite
|
Sign up to set email alerts
|

Air Reflux and Other Sequelae Following Endoscopic Dacryocystorhinostomy

Abstract: Treatment for epiphora with endoDCR results in air reflux in almost half of patients, which is minimally bothersome to patients. The presence of air reflux highly correlates with resolution of epiphora and has a similar incidence in external and endoDCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This communication appears to have led to the free retrograde reflux of both air and mucus from the nasal cavity directly to the surface of the eye. This effect is similar to that which may occasionally occur following dacryocystorhinostomy, or more commonly following canalicular bypass procedures, where a direct communication is deliberately created to overcome nasolacrimal obstructive symptoms 11 Submucosal diathermy to the inferior turbinate is a frequently performed procedure for hypertrophied inferior turbinate, with minimal complicationsSubmucosal diathermy can cause troublesome scarring around the nasolacrimal duct openingPatulous nasolacrimal duct stoma with reflux of air and mucus on to the ocular surface is a newly recognised complication of submucosal diathermyThis complication should be considered in pre-operative discussion…”
Section: Discussionmentioning
confidence: 71%
“…This communication appears to have led to the free retrograde reflux of both air and mucus from the nasal cavity directly to the surface of the eye. This effect is similar to that which may occasionally occur following dacryocystorhinostomy, or more commonly following canalicular bypass procedures, where a direct communication is deliberately created to overcome nasolacrimal obstructive symptoms 11 Submucosal diathermy to the inferior turbinate is a frequently performed procedure for hypertrophied inferior turbinate, with minimal complicationsSubmucosal diathermy can cause troublesome scarring around the nasolacrimal duct openingPatulous nasolacrimal duct stoma with reflux of air and mucus on to the ocular surface is a newly recognised complication of submucosal diathermyThis complication should be considered in pre-operative discussion…”
Section: Discussionmentioning
confidence: 71%
“…It is a non invasive test without any potential to damage the lacrimal system to which the authors found no discomfort and pain in this series and others. 8,9,11,12 It, however, may contaminate the ocular surface by potentially transferring the bacterial flora and mucosal debris from nose to the eye. Air bubble test was performed either by not putting any drop 8,11 or saline 9 on the eye without any report of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of positive ABT was similar in cases with and without common canalicular membranectomy (removal of Rosenmuller valve) during Ext-DCR procedure, implying that its presence was not related to 1-way valve action of Rosenmuller. 11 Furthermore, not having positive ABT in normal subjects 11,12 and a greater than normal pressure rise (after valsalva) in the lacrimal sac area after DCR procedure 13 suggest that valve of Hasner may protect the upper lacrimal system from excessive intranasal pressure 11 in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries caused by the rotating shaft of the burr are fortunately uncommon yet it can represent a serious complication following drilling procedures in extended endonasal surgeries such as dacryocystorhinostomia (DCR) and median maxillectomy (MM) 1,2 . In the worst case, these ulcers of the nasal vestibular skin not only cause transient post-operative pain but also anxiety and psychological problems 3 , nasal obstruction due stenosis and cosmetic problems by scar formation and retraction 4,5,6 .…”
Section: Introductionmentioning
confidence: 99%